Evaluation of simple sequence repeats (SSR) markers associated with resistance to Sclerotinia sclerotiorum (Lib.) de Barry in commercial South African soybean cultivars - Vorster, Barend Juan (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.